Portable Power: Examining the Impact of Portable Chargers on Electric Vehicle Adoption - Mayuresh Vaidya; Abhishek Bankar; Abhijeet Pardhi; Vanshita Parab; Vrushali Sonawane (International Journal of Advanced Control and System Engineering, 2024)
Although switching to electrified mobility presents issues for the electricity system, it offers a viable way to address climate change. Even with significant improvements in electric vehicle (EV) technology, the process of charging puts stress on current network infrastructure. To address these issues, the use of charging management techniques is recommended in this paper. It also explores how EVs might be integrated into the smart grid, highlighting possible benefits, especially in vehicle-to-grid (V2G) technology and reducing the intermittent nature of renewable energy. This study proposes a unique solution for emergency roadside charging assistance scenarios: a single-phase multipurpose EV on-board charger with improved vehicle-to-vehicle (V2V) functionality. This charger eliminates the need for extra portable chargers by supporting V2V operations with rated power, in contrast to standard configurations. MATLAB/Simulink is used for the charger's design and simulation, and a lab prototype is built to verify its main features.
Keywords: Battery and Charger technologies; Electric vehicle; Impacts; Portable; Powertrain; Promising approach; Proposed